Wood-base industry in Sarawak -furniture making; the level of readiness of the bumiputera furniture makers of the Kuching Division, Sarawak in facing AFTA / Adli Kiprawie - Kiprawie, Adli (2002)
The strength of Sarawak's economy has always been the primary sector because it has been blessed with abundance of natural resources. However, within the primary sector there was a shift in importance from an agro-based economy to oil and gas-based economy from the mid-eighties. A close look at the sectoral contribution has shown that the manufacturing sector is second in importance, bypassing the agricultural sector in the Sarawak economy since the nineties. The manufacturing sector is the most dynamic sector in Sarawak, just like for Malaysia as a whole. In 1978, it contributed 6.5 percent to the GDP and in 1993 it increased to 16.8 percent, and by 1996 to 21.3 percent (Statistic Department, 1998). It is presently the second biggest sector in Sarawak, next to mining and quarrying, although its contribution to total manufacturing output or manufacturing employment in Malaysia is below 5 percent.